FEATURES OF THE FORMATION OF STRESS RESISTANCE AS A COMPONENT OF THE MOTIVATIONAL READINESS OF FUTURE TEACHERS-ATHLETES FOR PROFESSIONAL ACTIVITIES - Almazova I.G. ,; Yelnikova O.E. ,; Kolosova I.G. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify and present the characteristics of the features of the formation of stress resistance as part of the motivational readiness of teachers-athletes for professional activities. Methods and structure of the study. Pilot-experimental work was carried out at the Federal State Budgetary Educational Institution of Higher Education “Bunin Yelets State University”. The respondents were students of 1-3 years of study; areas of training 49.03.01 Physical culture; 44.03.05 Pedagogical education (with two training profiles), focus (profile) Physical culture, Life safety; Physical culture and life safety, Technology. Accordingly, these respondents study in groups C-11, SB-31, SBT-11 of the Institute of Physical Culture, Sports and Life Safety of YSU. I.A. Bunin. Diagnosis was carried out using the technique of Shcherbatykh Yu.V.; Boston test for stress resistance; S. Cohen and G. Willianson's test; 5PFQ test (adapted by Heijiro Tsuya, translated by A.B. Khromov); methods "Value orientations" (O.I. Motkova, T.A. Ogneva), methods of K. Zamfir (modified by A. Rean). Results and conclusions. The results of the study of value orientations did not allow a clear separation of the most preferred values within the control and experimental groups. The results obtained made it possible to develop recommendations for the program of stress resistance formation in future teachers-athletes, also relying on the significant characteristics of professional activity and coping strategies that can be used in its implementation.